Physics Problem Based E-Module Development to Improve Studentâ€™s Physics Concept Understanding - Andi Ulfah Khuzaimah; Bunga Dara Amin; Kaharuddin Arafah (Jurnal Penelitian Pendidikan IPA, 2022)
This research was a development research that aims to: describe feasibility, practitioner assessment, effectiveness in learning, then produce a problem-based physics e-module. The subjects of this research were 33 students of class XI IPA MA DDI Alliritengae. This research used the ADDIE model development. The instruments that were used in this research were e-module validation sheets, practitioner response questionnaires (educators/teachers), and students' conceptual understanding test instruments. The eligibility criteria for e-modules can be seen from the aspect of validity. The practical criteria can be seen from the practitioner's assessment of the e-module, and the effectiveness criteria can be seen from the increasing students' concept understanding test results. Based on the results, it can be concluded: The developing problem-based physics e-module, based on expert judgment used the Aiken V index analysis, was declared valid and suitable for use with minor revisions; The problem-based physics e-module in terms of the response of physics teachers was in â€œvery goodâ€ category; The studentsâ€™ conceptual understanding ability analyzed with N-gain obtained an average value of 0.42 that was in the medium category which means that there was an increasing in students' conceptual understanding abilities so that it can be concluded that The problem-based physics e-module developed was effective in improving students' conceptual understanding skills